2008
DOI: 10.1007/s10865-007-9147-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medication regimen factors on adherence to chronic treatment: a review of literature

Abstract: This article reviews recent literature in chronic illness or long-term health management including asthma, contraception, diabetes, HIV disease, and hypertension/cardiovascular disease, mental disorders, pain, and other diseases to determine the relationship between regimen factors and adherence to medications. The authors conducted an electronic literature search to detect articles published between 1998 and 2007. Articles were included if they pertained to a chronic illness or to contraception, included a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
345
3
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(372 citation statements)
references
References 68 publications
17
345
3
7
Order By: Relevance
“…Similar to other studies also our data suggested that especially older men suspected lower adherence in treatment of prescribed medications [18]. As solution was suggested to choose medication with longer elimination of half period in this situation, which could allow patients with low adherence to reach optimal therapeutic efficiency [19].…”
Section: Int Conf Society Health Welfare 2014supporting
confidence: 88%
“…Similar to other studies also our data suggested that especially older men suspected lower adherence in treatment of prescribed medications [18]. As solution was suggested to choose medication with longer elimination of half period in this situation, which could allow patients with low adherence to reach optimal therapeutic efficiency [19].…”
Section: Int Conf Society Health Welfare 2014supporting
confidence: 88%
“…7 These findings and findings from other studies of the predictors of medication adherence [8][9][10][11][12][13][14][15][16] suggest a need to risk adjust for patient characteristics while computing adherence-based pharmacy quality scores. Failure to do so may result in comparisons that do not accurately reflect the effect of individual providers and rewards or penalties in pay-for-performance programs or other incentive/disincentive arrangements that may be reflective of the patient pool rather than pharmacy performance.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 93%
“…These include lack of patient knowledge, difficulty of treating an asymptomatic condition, personal beliefs that conflict with hypertension treatment goals, and other patient issues such as social economic status, cultural beliefs, access to care, psychosocial factors, and health literacy [5]. Additional obstacles include a lack of communication and trust between patients and care providers, high medication costs, high drug burden, failure to attend follow-up appointments, and discontinuation of therapy due to drug side effects [5][6][7][8][9][10]. There is limited data available about patients' personal perspectives regarding obstacles to hypertension control [11,12].…”
Section: Introductionmentioning
confidence: 99%